Sequence characteristics, expression and subcellular localization of PtCYP721A57 gene from cytochrome P450 family in Polygala tenuifolia willd - Luo, Yao; Hu, Benxiang; Ji, Haiyue; Jing, Yiyao; Zhang, Gang; Yan, Yonggang; Yang, Bingyue; Peng, Liang (PeerJ, 2024)
The Cytochrome P450 (CYP450) family is the largest enzyme protein family in plants, distributed across various organs and involved in significant catalytic activities in primary and secondary metabolic processes. In this study, we cloned the PtCYP721A57 gene, characterized its open reading frame (ORF), and conducted comprehensive analyses including physicochemical properties, evolutionary relationships, subcellular localization, prokaryotic expression, and correlation between the relative expression of different parts and the content of tenuifolin, hormones, and abiotic stress response associated with the encoded protein. The ORF of PtCYP721A57 was 1,521 bp, with a secondary structure predominantly composed of α-helices and random coils. Subcellular localization experiments confirmed the presence of PtCYP721A57 in the endoplasmic reticulum. For prokaryotic expression, we constructed the recombinant plasmid pET28a-PtCYP721A57 using pET28a as the vector, which was then transformed into BL21(DE3). Induction with Isopropyl β-D-1-thiogalactopyranoside (IPTG) at temperatures of 16 and 25 °C and varying concentrations (0.1, 0.2, 0.5, 1, 2 mM) resulted in the formation of inclusion bodies, with higher expression observed at 25 °C. Our qPCR analyses revealed that PtCYP721A57 exhibited the highest expression in the cortex of Polygala tenuifolia, followed by roots and xylem, correlating with the observed tenuifolin content distribution. Induction with abscisic acid (ABA) and chitosan (CHT) initially decreased PtCYP721A57 expression followed by a subsequent increase, peaking at 48 h. Similarly, drought stress induced a gradual increase in PtCYP721A57 expression, also peaking at 48 h. NaCl treatment for 6 h significantly upregulated PtCYP721A57 expression. In conclusion, our study provides foundational insights into the PtCYP721A57 gene in Polygala tenuifolia, laying the groundwork for further exploration of its role in the biosynthesis pathway of triterpenoid saponins.
Keywords: Polygala tenuifolia; Cytochrome P450; Gene cloning; Subcellular localization; Gene expression